Justice as a Principle of Criminal Law - V. V. Zhuravleva; I. V. Tertychnaya (Теоретическая и прикладная юриспруденция)
The article examines the essence of the principle of justice in Russian criminal law, its reflection in the norms of the criminal legislation of Russia, as well as the influence of this principle in sentencing.